Le classement des professions par secteurs d’activité : aperçu critique et présentation d’une nouvelle grille - Bouchard, Gérard; Pouyez, Christian; Roy, Raymond (L'Actualité économique)

(untitled) (HEC Montréal, 1979)
This article presents, in the first part, a critical review of the literature on this subject. In the second part, a new grid for the classification of occupations is constructed.